Synthesis, Characterization and Electrochemical Studies on the Interaction Mechanism between La(III) Complex and DNA - Ling Zhang, Xiu; Guo, Feng (Asian Journal of Chemistry, 2010)
The La(III) Schiff base complex was synthesized and characterized by elemental analysis, molar conductivity, IR and thermal decomposition. Cyclic voltammetry was used to investigate the interaction between La complex and DNA. The fundamental electrochemical characteristics of a La(III) complex have been studied and the interactivity of lanthanide complex with DNA was also studied by cyclic voltammetry and fluorescence spectrum. The results suggest that the binding ratio between the lanthanide complex and DNA was found to be 1:1 and the binding constant was 3.42 × 103 L mol-1.